(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This work presents a genealogy of psychological care developed around those affected by state terror in the Southern Cone and highli- ghts the importance of symbolic reparation as a public policy. Two unpublished experiences in Brazil and Argentina are taken as refe- rence, which developed a work of psychological and / or psychosocial accompaniment, attention and reparation as a way of processing the pain produced by the situations of torture, forced disappearance, kidnappings, persecutions, appropriation of girls and children and family losses. We are interested in investigating the incidences of State intervention when facing this pain and its effects, creating spaces and places of memory, managing public policies aimed to counteract these painful effects and the ways of organizing these policies, in the paradoxical circumstance of being responsible for the crimes caused and moreover in this specific universe of victims.